2020
DOI: 10.1007/s00216-020-02529-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of volatile metabolites from in vitro biofilms of Pseudomonas aeruginosa with thin-film microextraction by thermal desorption gas chromatography-mass spectrometry

Abstract: Cystic fibrosis (CF) is an autosomal recessive inherited disease which leads to a production of thickened mucus in the airways. These conditions are conducive to poly-microbial infections, like chronic lung infection, in which Pseudomonas aeruginosa (P. aeruginosa) is the major pathogenic bacterium colonizing CF lungs at the end of the lifetime of CF patients. This in vitro study uses a P. aeruginosa biofilm model under partly cystic fibrosis conditions, with a sampling of volatile extracellular metabolites. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…All these differences in findings are incompletely resolved, and require further study. An important observation in other prior studies is that there can be considerable variation in the production of different volatiles among various Pa strains [64,67,71,72]; culture conditions also affect the spectrum of Pa volatiles produced [61,67,72,76]. It is also possible that vapors from some of the Af media they used interacted with the Pa volatiles, which may explain the differences [57,62] from our results.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…All these differences in findings are incompletely resolved, and require further study. An important observation in other prior studies is that there can be considerable variation in the production of different volatiles among various Pa strains [64,67,71,72]; culture conditions also affect the spectrum of Pa volatiles produced [61,67,72,76]. It is also possible that vapors from some of the Af media they used interacted with the Pa volatiles, which may explain the differences [57,62] from our results.…”
Section: Discussionmentioning
confidence: 46%
“…Many of the volatiles of interest to us as potential Pa inhibitors (Table 3) have been noted previously among Pa volatiles, including 2-undecanone [57,[63][64][65][66][67]71,76], 2-heptanone [64][65][66][67]71,76], and methyl thiocyanate [67]. 2-heptanone has been noted to be an inhibitor of micro-organisms (bacteria) [78].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Second, our data show that the growth phase of the organism has a strong influence on the volatilome, and therefore, using in vitro culture conditions that can most closely replicate the in vivo environment and microbial growth phases may increase the likelihood of putative biomarker translation from bench to bedside. In addition to controlling the growth phase of dimorphic organisms, macronutrient, micronutrient, and oxygen availability should all be considered in the development of in vitro model systems that replicate the in vivo physiology of the pathogen ( 14 , 17 , 36 – 41 ). In this study, we observed 35 VOCs present in at least 67% of all spherule strains ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our data show that the growth phase of the organism has a strong influence on the volatilome, and therefore using in vitro culture conditions that can most closely replicate the in vivo environment and microbial growth phases may increase the likelihood of putative biomarker translation from bench to bedside. In addition to controlling the growth phase of dimorphic organisms, macronutrient, micronutrient, and oxygen availability should all be considered in the development of in vitro model systems that replicate in vivo physiology of the pathogen (14, 17, 27, 30, 33, 36, 52, 53). Our next step in developing a Valley fever breath test is to translate in vitro biomarkers for use with an in vivo mouse model.…”
Section: Discussionmentioning
confidence: 99%